How ChatGPT shapes a new reality of writing: Is there a place for humans in an artificial world? - Veronika Yurchenko; Oleksii Nalyvaiko (Educational Challenges)
Aim. This study explores the impact of Artificial Intelligence (AI) -driven text generation on authorship recognition and its implications for education. Specifically, it examines how individuals with varying levels of experience using ChatGPT perceive AI-generated texts and whether editing affects their ability to distinguish between human and AI-authored content. The study aims to inform strategies for integrating AI literacy into education while addressing challenges in authorship attribution.